Pengembangan Media Pembelajaran (FlashCard) Matematika Berdasarkan Kreativitas Mahasiswa PGMI - Azura, Wan; Sari, Ira; Mursida, Mursida (Paedagogie, 2026)
The research aims to develop flashcard learning media based on the creativity of prospective elementary school teacher students in creating mathematics flashcard learning media. This type of research uses the R&D (Research & Development) method with the application of the ADDIE approach, namely analysis, design, development, implementation, and evaluation. Research for flashcard implementation uses a pre-experimental design with one-shot case study Design. Sample selection is done by purposive sampling technique, the sample studied is elementary school students 05 Sam-sam, Kandis grade 5 who take tutoring at Pondok Cerdas Zhafira. Based on the results of the flashcard media that have been made by PGMI students, describing the students' creativity abilities through aspects of fluency of thinking, flexibility, elaboration and originality is classified as good, because it has provided ideas and material coverage simply with innovative examples, exercises and answer keys on the flashcard. Based on the feasibility analysis obtained in the form of content feasibility with a result of 3.4, language feasibility is 3.25, presentation feasibility obtained a value of 3.75, while graphic feasibility obtained a value of 4, so the flash card learning media is suitable for use as a mathematics learning media. The use of flashcards in learning activities by fifth grade students of SD 05 Sam-sam obtained an average value of 80.36, more than the KKM value of 75.00 and a one-sample t-test hypothesis test obtained significant results (0.000 <0.05) which means that the flashcard media for geometric shapes has an effect on mathematics learning, because students are interested and enthusiastic in learning.